Ultrasonographic Diagnosis of Diastematomyelia During the 14th Week of Gestation - Kazşm Emre Karaşahin; Kazım Gezginç; Ibrahim Alanbay; Mustafa Ulubay; Iskender Başer (Elsevier, 2009)
Objective: We present a case of type I diastematomyelia diagnosed with ultrasonography at the 14th week of gestation. Case Report: A 26-year-old primigravida at 14 weeks' gestation was presented to our outpatient department with a complaint of dysuria. Routine antenatal ultrasound revealed disruption of the fetal upper thoracic vertebral column curvature, together with hemivertebrae. Further high-resolution two-dimensional ultrasound examination revealed dilatation of the thoracolumbar vertebrae and extra echogenic foci in the spinal canal. Thoracolumbar meningocele was also observed. These observations (thoracic hemivertebrae, scoliosis and thoracolumbar meningocele) suggested a diagnosis of type I diastematomyelia. The family was counseled regarding the prognosis for the fetus. Their decision to terminate the pregnancy was considered and approved by the ethical council. The postabortion pathologic examination, along with X-ray, three-dimensional computed tomography and magnetic resonance imaging examinations, supported the initial diagnosis. Conclusion: Prenatal diagnosis of diastematomyelia during the 14th week of pregnancy is possible using high-resolution ultrasound. To the best of our knowledge, this is the earliest case presented in the literature.